Penerapan Metode Multi-Factor Evaluation Process dalam Penilaian Dosen - Wahidin, Ahmad Jurnaidi (LPPM STT Terpadu Nurul Fikri, 2024)
Lecturer performance evaluation is a crucial component in improving the quality of higher education. This study examines the application of the Multi-Factor Evaluation Process (MFEP) method in evaluating lecturers' performance at Universitas Bina Sarana Informatika. The aspects assessed include pedagogical, professional, personal, and social factors. Data were collected through Likert-scale-based questionnaires distributed to students. The MFEP method was employed to process the evaluation data, considering each aspect's weight and evaluation factors. The analysis results show that the professional aspect received the highest weight, followed by the pedagogical, personal, and social aspects. The lecturer with the best performance (Alternative A2) recorded the highest evaluation score of 4.44, indicating excellence across all evaluated aspects. This study concludes that MFEP is an effective method for providing objective and holistic lecturer performance assessments. Therefore, this method can give lecturers constructive feedback and improve teaching quality. The study recommends applying MFEP at other higher education institutions to ensure the method's consistency and accuracy in various educational contexts.